2021
DOI: 10.1021/acsami.0c21151
|View full text |Cite
|
Sign up to set email alerts
|

ROS-Responsive Nanoparticle as a Berberine Carrier for OHC-Targeted Therapy of Noise-Induced Hearing Loss

Abstract: Overproduction of reactive oxygen species (ROS) and inflammation are two key pathogeneses of noise-induced hearing loss (NIHL), which leads to outer hair cell (OHC) damage and hearing loss. In this work, we successfully developed ROS-responsive nanoparticles as berberine (BBR) carriers (PL-PPS/BBR) for OHC-targeted therapy of NIHL: Prestin-targeting peptide 2 (PrTP2)-modified nanoparticles (PL-PPS/BBR), which effectively accumulated in OHC areas, and poly(propylene sulfide) 120 (PPS 120 ), which scavenged ROS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 50 publications
(85 reference statements)
0
32
0
Order By: Relevance
“…Moreover, a recent anatomical study of the human cochlea revealed that perforated structures at the modiolar surface of the scala tympani (ST) and the scala vestibuli (SV) allowed fluid exchanges between the modiolar space/vascular tree, the perilymph, and the spiral ligament ( Rask-Andersen et al, 2006 ). Our nanoparticles, with a diameter of 5 nm, are much smaller than those used in other experiments (diameter >200 nm) ( Zhao et al, 2021 ). These results suggest that the size of nanoparticles affects absorption, and drugs with a small size in the perilymph reach the modiolus or limbus more easily.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Moreover, a recent anatomical study of the human cochlea revealed that perforated structures at the modiolar surface of the scala tympani (ST) and the scala vestibuli (SV) allowed fluid exchanges between the modiolar space/vascular tree, the perilymph, and the spiral ligament ( Rask-Andersen et al, 2006 ). Our nanoparticles, with a diameter of 5 nm, are much smaller than those used in other experiments (diameter >200 nm) ( Zhao et al, 2021 ). These results suggest that the size of nanoparticles affects absorption, and drugs with a small size in the perilymph reach the modiolus or limbus more easily.…”
Section: Resultsmentioning
confidence: 85%
“…The loading content (%) and loading efficiency (%) of Au-DENPs-Dex were measured by high-performance liquid chromatography [HPLC (Thermo Fisher U3000)] at following time points: 0.5, 1, 3, 5, 8, 24, 48, and 72 h ( Yoon et al, 2015 ). The test conditions were as follows: a series of Dex solutions with different concentrations (1,000, 500, 250, 125, 62.5, 31.25, 15.6, 7.8, and 3.9 μg/m L), a mobile phase of water and acetonitrile (60:40 v/v), sample injection volume of 20 μL, flow rate of 1.0 ml/min, column temperature of 30°C, and detection wavelength of 240 nm ( Zhao et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(C) PPS 120 converted to poly(propylene sulfoxide) 120 and released drug in an ROS environment. Reproduced with permission ( Zhao et al, 2021 ). Copyright 2021 American Chemical Society.…”
Section: The Mechanism Of Reactive Oxygen Species-responsive Biomaterialsmentioning
confidence: 99%
“…When simulated the ROS environment with 1 mM H 2 O 2 , a fast release of berberine (BBR) was observed from PL-PPS/BBR at 48 h ( Figure 2C ). During this progress, PPS 120 scavenged ROS and converted to poly(propylene sulfoxide) 120 when reacted with ROS to obtain the rapid release of BBR ( Zhao et al, 2021 ). Thioether-containing polymers contribute an effective method for loading and delivering hydrophobic drugs especially for the application of cancer therapy.…”
Section: The Mechanism Of Reactive Oxygen Species-responsive Biomaterialsmentioning
confidence: 99%